(untitled) (Sahel Journal of Life Sciences FUDMA, 2025)
This study investigated the physicochemical properties of cassava flour (lafun) fortified with Bambara nut flour. Cassava tubers and Bambara nut seeds were fermented and processed into flour. The processed flours were formulated into five samples and designated as CAS1 (100:0), CASBAM2 (95:5), CASBAM3 (90:10), CASBAM4 (85:15), and CASBAM5 (80:20) for cassava and Bambara nut, respectively. The functional, proximate, mineral, and vitamin of the flour blends were evaluated using standard methods. The flour blends were used to produce stiff paste and the sensory properties were evaluated using the 9-point hedonic scale. The results showed that there were significant (p<0.05) differences in the various attributes analyzed. The proximate results ranged from 11.77 to 12.67% (moisture), 1.05-3.67% (crude protein), 0.38-2.12% (fat), 4.02-4.50% (crude fibre), 1.47-2.46% (ash), and 75.52 - 80.42% (carbohydrate). The energy value also ranged from 329.28 to 335.82 kcal/100g. The functional properties of the flour blends showed significant differences (p<0.05). The mineral ranged from 18.97 to 20.46 mg/100g (magnesium), 23.33 to 25.13mg/100g (potassium), 2.16 to 2.50mg/100g (iron), 36.74 to 37.66mg/100g (calcium), and 0.27 to 0.71mg/100g (sodium). The vitamin contents of the samples were significantly different (p<0.05). The sensory results depict that the stiff paste samples were liked and accepted since the scores recorded were above 6 in all the attributes assessed, which translates to like moderately and like very much in the hedonic scale. Bambara nut fortification enhanced the nutrient content of the composite flour samples, hence, its use in the production of lafun should be encouraged.